Retropupillary fixation of Iris-claw intraocular lens versus transscleral suturing fixation for aphakic eyes without capsular support - Hara, Shuya; Borkenstein, Andreas; Ehmer, Angela; Auffarth, Gerd U. (Journal of refractive surgery, 2011)
PURPOSE:Retropupillary fixation of an iris-claw intraocular lens (IOL) (Verisyse, Abbott Medical - Optics) was performed for aphakic eyes without sufficient capsular support, and safety - and recovery of the procedure were compared with transscleral suturing ...
Gesehen am 02.08.2022
Presented at the 23rd Annual Meeting of the Japanese Society of Cataract and Refractive Surgery; June 20–22, 2008; Tokyo, Japan